MENCIPTAKAN EKONOMI KREATIF DENGAN LAPORAN KEUANGAN YANG SEDERHANA UNTUK MENINGKATKAN PENDAPATAN UMKM - Nawawi; 2Lina Oktavia; 3Olivia Dwi Puspita; 4Anip Solihin (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2025)
This Community Service (PKM) aims to improve the understanding of making financial reports in Walantaka Tofu MSMEs in Kp. Tegal Kembang, Serang City, Banten Province, through training and assistance in preparing simple financial reports. The method used was sosialisasis and question and answer sessions, including preparation, implementation, and evaluation stages. The program results showed an increase in MSME owners' understanding of the preparation of simple financial statements that can help in making business decisions and financial planning.